2015
DOI: 10.1371/journal.ppat.1004483
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Flagella: Twist and Stick, or Dodge across the Kingdoms

Abstract: The flagellum organelle is an intricate multiprotein assembly best known for its rotational propulsion of bacteria. However, recent studies have expanded our knowledge of other functions in pathogenic contexts, particularly adherence and immune modulation, e.g., for Salmonella enterica, Campylobacter jejuni, Pseudomonas aeruginosa, and Escherichia coli. Flagella-mediated adherence is important in host colonisation for several plant and animal pathogens, but the specific interactions that promote flagella bindi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
129
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 157 publications
(133 citation statements)
references
References 108 publications
1
129
0
3
Order By: Relevance
“…Flagellum-promoted swimming motility is often a hallmark characteristic of planktonic bacteria in their exponential growth phase [49, 50]. To study the role of the flagellum in NET formation we used flagellum-deficient PAO1 and PAK strains (PAO1 fliC and PAK flgC ).…”
Section: Resultsmentioning
confidence: 99%
“…Flagellum-promoted swimming motility is often a hallmark characteristic of planktonic bacteria in their exponential growth phase [49, 50]. To study the role of the flagellum in NET formation we used flagellum-deficient PAO1 and PAK strains (PAO1 fliC and PAK flgC ).…”
Section: Resultsmentioning
confidence: 99%
“…Another motif of FliC, called flgII-28, is recognized independently of FLS2 by tomato and other solanaceous plants (but not by Arabidopsis), most likely via another pattern recognition receptor (24). Since these discoveries, it has been speculated that bacteria may escape recognition by variation or modification (decoration, e.g., glycosylation) of key flagellin residues, downregulation of flagellin expression, loss of the flagellum, or bacteria-driven enzymatic degradation of flagellin (111). Variations in Flg22 residues required for FLS2-mediated recognition are observed in xanthomonads, allowing evasion of FLS2-mediated immunity (128).…”
Section: Evasion Of Microbe-associated Molecular Pattern Recognition mentioning
confidence: 99%
“…Cultureindependent bioinformatic analysis could be used as a tool in finding candidate SFB functional genes. There are a large number of publications regarding flagellummediated adherence (15), and some studies demonstrated that flagellin has a role in regulating Th17 cell differentiation (16,17), IgA plasma cell generation, and Th1 functions (18). Comparative genomic analyses indicated that there is a set of genes that encode flagellin proteins within SFB genomes (19,20) and that the homology between SFB flagellin proteins is conserved in comparison to the most closely related Clostridium species (19).…”
mentioning
confidence: 99%